Enhanced CO2 photocatalytic conversion into CH3OH over visible‐light‐driven Pt nanoparticle-decorated mesoporous ZnO–ZnS S-scheme heterostructures. Issue 19 (1st October 2021) - Mohamed, Reda M.; Mkhalid, Ibraheem A.; Alhaddad, Maha; Basaleh, Amal; Alzahrani, Khalid A.; Ismail, Adel A.
Abstract: In the present contribution, the design and fabrication of Pt nanoparticle-decorated mesoporous ZnO–ZnS heterostructures were described and used effectively for photocatalytic CO2 conversion to yield CH3 OH. TEM images of the mesoporous Pt/ZnS–ZnO heterostructure demonstrated spherical ZnO NPs 20 nm, and Pt NPs 3 nm were well dispersed on the porous ZnS–ZnO heterostructure. The formation of CH3 OH over the Pt/ZnS–ZnO heterostructure was 78, 39 and 20 times larger than that bare ZnS, ZnO NPs and ZnS–ZnO, respectively. The optimal Pt/ZnO–ZnS heterostructure exhibited a high CH3 OH formation rate of 81.1 μmolg -1 h -1, which is about 44, 22 and 20 times larger than that of bare ZnS (1.86 μmolg -1 h -1 ), ZnO (3.72 μmolg -1 h -1 ), and ZnO–ZnS (4.15 μmolg -1 h -1 ), respectively. The significantly enhanced reduction of CO2 was imputed to the synergistic effects of the ZnO–ZnS heterostructure and the incorporation of Pt NPs. The synthesized photocatalyst provides a new transfer route through which carriers can migrate to the outer surface as well as pore channels of the mesoporous ZnO–ZnS, therefore significantly minimizing the transfer distance for carriers, inhibiting photoinduced electron-hole recombination, and diminishing the mobility resistance, as determined using photoluminescence, photocurrent response, and electrochemical impedance spectra measurements.